Essentials of athletic injury management - Prentice, William E. PhD, ATC, PT, FNATA
The eleventh edition of Essentials of athletic Injury Management provides the reader with the most current information on the subject of prevention and basic acre of sports injuries. The general philosophy of the text is that adverse effects of physical activity arising from participation in sport should be prevented to the greatest extent possible. However, the nature of participation in physical activity dictates that sooner or later injury may occur. In these situations, providing immediate and correct care can minimize the seriousness of an injury. Overall, this text is designed to take the beginning student from general to specific concepts. Each chapter focuses on promoting an understanding of the prevention and care of athletic injuries.